1993
DOI: 10.1177/002076409303900305
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenic Delusions Among Koreans, Korean-Chinese and Chinese: a Transcultural Study

Abstract: In this transcultural study of schizophrenic delusions among Koreans, Korean-Chinese and Chinese, many delusions were shown to be different among the three groups in their frequency and content and the differences could be explained by sociocultural and political factors. Delusional themes sensitive to influence by sociocultural or political situations and changes seem to be 'family', 'love affairs', 'religious matters', 'economic matters', 'specific physical damage' and 'political themes.' Delusions about 'fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 1 publication
5
22
0
1
Order By: Relevance
“…In comparison with 1912, Steinebrunner et al [13] pointed out that the type of poison increased in variety to include smoke damage and narcotic drugs. Fujimori [3] in Japan and Kim [4] in Korea attributed the lower incidence of delusions of poisoning in their countries as compared with China to the difference in the history of culture involving food and poison. The Japanese term 'Doku', meaning poison, is originally restricted to food alone, while the German term 'Gift' has a more extensive meaning including poison gas, etc.…”
Section: Themes Of Delusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with 1912, Steinebrunner et al [13] pointed out that the type of poison increased in variety to include smoke damage and narcotic drugs. Fujimori [3] in Japan and Kim [4] in Korea attributed the lower incidence of delusions of poisoning in their countries as compared with China to the difference in the history of culture involving food and poison. The Japanese term 'Doku', meaning poison, is originally restricted to food alone, while the German term 'Gift' has a more extensive meaning including poison gas, etc.…”
Section: Themes Of Delusionmentioning
confidence: 99%
“…The latter may derive from the grouporiented self in Japanese 'shame culture'. There are only limited data on the contents of schizophrenic delusions compared among different cultural areas [1][2][3][4]. Previous studies on this issue were carried out from the Western viewpoint, only covering patients in developing countries such as Africa or Java [5], or based on questionnaires with unspecified diagnostic criteria.…”
mentioning
confidence: 99%
“…He called delusions of persecution and grandiosity 'typical', 'fundamental' or 'primordial delirium'. The significance of these two themes in the context of schizophrenic delusions is confirmed by transcultural comparative studies [21,[29][30][31]. Each of them showed that persecution is the most frequent delusional theme, followed by grandiosity.…”
Section: Discussionmentioning
confidence: 78%
“…The basic hypothesis could be that there are only a few themes that can be found in all periods and cultures. These contents are persecution, grandiosity, religion, guilt, hypochondria, jealousy and love [3,4,21,29,30,32]. They seem to be of an extraordinary anthropological importance for the experience of the world and the person, for the organization of human relationships and the expression of hopes and fears, which are important especially in pathological conditions like schizophrenic delusions.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the effect of sociodemographic and cultural variables on types of delusions have be investigated (3)(4)(5)(6)(7)(8). Results of these studies support the view that, even though patients in different cultures show similar clinical presentations, the content of their symptoms can be traced back to regional or cultural themes.…”
mentioning
confidence: 99%